The role of optic nerve sheath diameter ultrasound in brain infection - Stead, GA; Cresswell, FV; Jjunju, S; Oanh, PKN; Thwaites, G; Donovan, J (Elsevier, 2021)
Brain infections cause significant morbidity and mortality worldwide, especially in resource-limited settings with high HIV co-infection rates. Raised intracranial pressure [ICP] may complicate brain infection and worsen neurological injury, yet invasive ICP monitoring is often unavailable. Optic nerve sheath diameter [ONSD] ultrasound may allow detection of raised ICP at the bedside; however, pathology in brain infection is different to traumatic brain injury, in which most studies have been performed. The use of ONSD ultrasound has been described in tuberculous meningitis, cryptococcal meningitis and cerebral malaria; however correlation with invasive ICP measurement has not been performed. Normal optic nerve sheath values are not yet established for most populations, and thresholds for clinical intervention cannot be assumed to match those used in non-infective brain pathology. ONSD ultrasound may be suitable for use in resource-limited settings by clinicians with limited ultrasound training. Standardisation of scanning technique, consensus on normal ONSD values, and action on abnormal results, are areas for future research. This scoping review examines the role of ONSD ultrasound in brain infection. We discuss pathophysiology, and describe the rationale, practicalities, and challenges of utilising ONSD ultrasound for brain infection monitoring and management. We discuss the existing evidence base for this technique, and identify knowledge gaps and future research priorities.